Melt‐rock interactions and fabric development of peridotites from North Pond in the Kane area, Mid‐Atlantic Ridge: Implications of microstructural and petrological analyses of peridotite samples from IODP Hole U1382A. (24th June 2016) - Harigane, Yumiko; Abe, Natsue; Michibayashi, Katsuyoshi; Kimura, Jun‐Ichi; Chang, Qing
Abstract: North Pond is an isolated sedimentary pond on the western flank of the Kane area along the Mid‐Atlantic Ridge. Drill‐hole U1382A of IODP Expedition 336 recovered peridotite and gabbro samples from a sedimentary breccia layer in the pond, from which we collected six fresh peridotite samples. The peridotite samples came from the southern slope of the North Pond where an oceanic core complex is currently exposed. The samples were classified as spinel harzburgite, plagioclase‐bearing harzburgite, and a vein‐bearing peridotite that contains tiny gabbroic veins. No obvious macroscopic shear deformation related to the formation of a detachment fault was observed. The spinel harzburgite with a protogranular texture was classified as refractory peridotite. The degree of partial melting of the spinel harzburgite is estimated to be ∼17%, and melt depletion would have occurred at high temperatures in the uppermost mantle beneath the spreading axis. The progressive melt–rock interactions between the depleted spinel harzburgite and the percolating melts of Normal‐Mid Ocean Ridge Basalt (N‐MORB) produced the plagioclase‐bearing harzburgite and the vein‐bearing peridotite at relatively low temperatures. This implies that the subsequent refertilization occurred in an extinct spreading segment of the North Pond after spreading at the axis. Olivine fabrics in the spinel and plagioclase‐bearing harzburgites are of types AG, A, and D, suggesting the remnants of a mantle flow regime beneath the spreading axis. The initial olivine fabrics appear to have been preserved despite the later melt–rock interactions. The peridotite samples noted above preserve evidence of mantle flow and melt–rock interactions beneath a spreading ridge that formed at ∼8 Ma. Key Points: Melt‐rock interactions formed plagioclase‐bearing harzburgite and vein‐bearing peridotite Melt‐impregnated harzburgite preserved olivine fabric of the host spinel harzburgite Peridotite preserved records of mantle flow and melt–rock interactions beneath spreading ridge at ∼8 Ma